Wing bone geometry reveals active flight in Archaeopteryx - Voeten, Dennis F A E; Cubo, Jorge; de Margerie, Emmanuel; Röper, Martin; Beyrand, Vincent; Bureš, Stanislav; Tafforeau, Paul; Sanchez, Sophie (Nature communications, 2018)
Archaeopteryx is an iconic fossil taxon with feathered wings from the Late Jurassic of Germany that occupies a crucial position for understanding the early evolution of avian flight. After over 150 years of study, its mosaic anatomy unifying characters of both non-flying dinosaurs and flying birds has remained challenging to interpret in a locomotory context. Here, we compare new data from three Archaeopteryx specimens obtained through phase-contrast synchrotron microtomography to a representative sample of archosaurs employing a diverse array of locomotory strategies. Our analyses reveal that the architecture of Archaeopteryx's wing bones consistently exhibits a combination of cross-sectional geometric properties uniquely shared with volant birds, particularly those occasionally utilising short-distance flapping. We therefore interpret that Archaeopteryx actively employed wing flapping to take to the air through a more anterodorsally posteroventrally oriented flight stroke than used by modern birds. This unexpected outcome implies that avian powered flight must have originated before the latest Jurassic.
Keywords: zkameněliny; X-Ray Microtomography; křídla zvířecí; Biological Evolution; Bone and Bones; let zvířat; Animals; ptáci; rentgenová mikrotomografie; kosti a kostní tkáň; Birds; dinosauři; Dinosaurs; zvířata; biologická evoluce; Wings, Animal; Flight, Animal; Fossils